CHARACTERISTICS OF THE BOARD OF COMMISSIONERS, COMMITTEES AND DISCLOSURE OF COMPANY RISK - Falendro, Andre; Faisal, Faisal; Ghozali, Imam (Jurnal Reviu Akuntansi dan Keuangan)
This study examines the influences of board of commissioneer and committee characteristics on the extent of enterprise risk management disclosure. The sample consists of  168 non-financial companies listed on Indonesia Stock Exchange for period of 2014-2016. A risk disclosure index is used to measure the extent of such disclosure. The results show that the presence risk management committee has a significant effect on the extent of risk disclosure. However, other board and committee characteristics doesn’t have significant influence on risk disclosure. The result of this suggests that corporate governance mechanisms, specifically board and audit committee have not fully explained their role in enhancing transparency, especially in communicating corporate risks.